Subacute thyroiditis post viral vector vaccine for COVID-19. (2nd September 2022) - Casey, Caoimhe; Higgins, Tom
Abstract : Summary: Subacute thyroiditis is an inflammatory disorder of the thyroid gland that has previously been described following viral illnesses and occasionally post vaccination such as influenza vaccine. 2021 was a revolutionary year for the development of SARS-CoV-2 vaccinations with multiple different vaccines now available. There are increasing numbers of case reports of thyroiditis following these vaccinations. We report a case of a 50-year-old female who developed subacute thyroiditis 6 days post ChAdOx1 nCoV-19 vaccine (AZD1222 produced by AstraZeneca Vaxzevria). The initial thyrotoxic phase was followed by overt hypothyroidism. This resolved spontaneously within 5 months without levothyroxine replacement. We hope that our case will add to the growing literature of cases of thyroiditis occurring after multiple different types of SARS-CoV-2 vaccination and create awareness of this rare but treatable adverse effect. We also review the literature on the proposed mechanisms behind this adverse effect. Learning points: Subacute thyroiditis is an inflammatory disorder of the thyroid gland that can occur after a viral illness or vaccination against certain infections. Subacute thyroiditis is a rare adverse effect that has been reported to occur after different types of SARS-CoV-2 vaccinations. Subacute thyroiditis post vaccination is relatively straightforward to manage, with some patients requiring non-steroidal anti-inflammatory drugs and beta-blockers, while more severe cases may require corticosteroid therapy. This adverse effect should not dissuade vaccination use at a population level. There are many postulated mechanisms for the development of subacute thyroiditis following vaccination including the presence of the ACE-2 receptor for SARS-CoV-2 on the thyroid gland, an inflammatory/immune response as is seen in COVID-19 infection itself and molecular mimicry between SARS-CoV-2 spike protein and healthy thyroid antigen.